The Influence Of Facilities And Infrastructure, Competency, Training On The Performance Of Employees Of The Women's Empowerment And Child Protection Office Of Samarinda City - Anis Qomariyah; Joko Sabtohadi; Vera Anitra; Muhammad Harry Rahmadi (Sean Institute, 2024)
There is findings , based on plan strategic 2021-2026 about inadequate facilities and infrastructure adequate in support walk maximum performance employee development Study This aim to see the impact facilities and infrastructure on performance , competency on performance , influence training on performance and which variables influence it most performance Samarinda City Women 's Empowerment and Child Protection (DP2PA ) employee . This research uses approach quantitative with 44 samples of all employees . Method data collection using offline and online questionnaires . Data analysis in research This is multiple linear regression . Acquisition study shows that Facilities and Infrastructure variables influential positive significant to performance employee , variable competencies and variables training No influential significant to performance employee . Then dominant variable is variable competence , and so on coefficient determination with mark 0.438 (43.8%) whereas the rest amounting to 0.562 (56.2%) influenced by variables other.